Whether COVID-19 has waterborne transmission too? - Chandra Mohan Kumar; Bhabesh Kant Chowdhry; Shweta Singh (Wolters Kluwer Medknow Publications, 2021)
SARS CoV-2 and COVID-19 have hogged the headlines for almost 18 months and over the last 2 months, it has occupied the mind space of entire India. Its second wave has not only sent shock waves across the nation but has created ripples across oceans too. There has been intense debate over how it went spiralling up in such a manner that India is is reporting large number of cases daily as well as deaths. One of most hotly debated topics is "Whether it is being transmitted through contaminated water too?" There is enough evidence that the virus sheds in feces and that the virus sheds in feces, sewage, sewer lines, waste water, and sewage treatment plants as well as effluents of plants. The important factor is that about two-third of sewer is not treated. On top of that, countries such as India do not have universal access to safe drinking water and practice of open defecation is still prevalent. In such a scenario, likelihood of waterborne transmission cannot be ruled out.